OPTIMALISASI PERAN PEMBIAYAAN PRODUKTIF BANK SYARIAH BAGI UMKM DI INDONESIA - Trimulato, Trimulato; K., Amiruddin; Ismawati, Ismawati; Nuraeni, Nuraeni (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2020)
Productive financing are very important in Indonesia, considering that in Indonesia there are around 52 million MSMEs . This study aims to determine the development and optimization of productive financing products in Islamic Banks towards MSMEs.This research is qualitative by using documentation techniques in data collection. Data analysis was performed using qualitative procedures. The results of this study found that the optimization of productive financing of Islamic Banks for MSMEs is still not optimal due to the financing of Islamic banks for MSMEs not being a priority and financing of Islamic banks in the consumer sector is still dominant.